Measurement of mechanical loads in large wind turbines: Problems on calibration of strain gage bridges and analysis of uncertainty. Issue 12 (24th August 2017) - Bezziccheri, M.; Castellini, P.; Evangelisti, P.; Santolini, C.; Paone, N.
Abstract: The paper discusses the complexity of calibration of strain gage full bridges applied to measure mechanical loads in large wind turbines, when direct application of calibration loads is not feasible. In particular, at first, it presents a generalized static‐dynamic mechanical model which allows to calibrate the strain gage full bridges using its own unbalanced masses to generate known reference inputs. Then, the paper discusses the uncertainty associated to such a calibration, according to the ISO/IEC Guide 98‐3:2008 "Guide to the Expression of Uncertainty in Measurement". The uncertainty of the reference input and the following calibration is discussed, which is often larger than the target set by the standard IEC‐61400‐13 used for wind turbine type certification. The paper comments on the attainable range of calibration which is rather limited with respect to expected load range in operation. Even if calibration should take place in isothermal effects, this is not always the case in real world practice. Therefore, the thermal effects on strain gage bridges are also discussed, putting into evidence its influence on calibration uncertainty both for full bridges in T configuration and in parallel configuration.